2011
DOI: 10.1186/1472-6963-11-138
|View full text |Cite
|
Sign up to set email alerts
|

Managing resources in NHS dentistry: using health economics to inform commissioning decisions

Abstract: BackgroundThe aim of this study is to develop, apply and evaluate an economics-based framework to assist commissioners in their management of finite resources for local dental services. In April 2006, Primary Care Trusts in England were charged with managing finite dental budgets for the first time, yet several independent reports have since criticised the variability in commissioning skills within these organisations. The study will explore the views of stakeholders (dentists, patients and commissioners) rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…This study also showed that direct operational costs with human resources were found to account for the greatest share of the total cost (84.7%) and variable costs were observed to account for 8.5% in 2012, as also found by other authors 7 , 10 , 15 . Human resource costs have represented from 66.4% to 79.4% of the total cost 10 . Variable costs (consumables), in turn, have been from 9.8% to 10.3% 7 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study also showed that direct operational costs with human resources were found to account for the greatest share of the total cost (84.7%) and variable costs were observed to account for 8.5% in 2012, as also found by other authors 7 , 10 , 15 . Human resource costs have represented from 66.4% to 79.4% of the total cost 10 . Variable costs (consumables), in turn, have been from 9.8% to 10.3% 7 .…”
Section: Discussionsupporting
confidence: 88%
“…Besides that, Asi Index system of Salvador’s Municipal Health Care Office may also always have lower prices under the smallest price logic in public procurement processes. In this sense, the studies reinforce the need to include capital cost analysis to calculate the total cost, and this capital cost is essential 7 , 8 , 10 .…”
Section: Discussionmentioning
confidence: 95%
“…An overview of our approach and research methods are outlined in our published study protocol. 24 The study received a favourable ethical opinion from County…”
Section: Methodsmentioning
confidence: 99%
“…12,14,15 The research was designed to follow the stages inherent to traditional PBMA exercises ( Table 1). The PBMA research meetings with participants and the methods involved are detailed in our study protocol 24 and Table Participants RH invited all NHS commissioners (those with responsibility for managing local NHS dental services) in the chosen organisation and selected local NHS dentists identified by the commissioning organisation's 'dental practice advisor' to participate.…”
Section: Designmentioning
confidence: 99%